Security patterns in practice : designing secure architectures using software patterns - Fernandez, Eduardo B. (Wiley series in software design patterns, 2013)
Learn to combine security theory and code to produce secure systems Security is clearly a crucial issue to consider during the design and implementation of any distributed software architecture. Security patterns are increasingly being used by developers who take security into serious consideration from the creation of their work. Written by the authority on security patterns, this unique book examines the structure and purpose of security patterns, illustrating their use with the help of detailed implementation advice, numerous code samples, and descriptions in UML. * Provides an extensive, up-to-date catalog of security patterns * Shares real-world case studies so you can see when and how to use security patterns in practice * Details how to incorporate security from the conceptual stage * Highlights tips on authentication, authorization, role-based access control, firewalls, wireless networks, middleware, VoIP, web services security, and more * Author is well known and highly respected in the field of security and an expert on security patterns Security Patterns in Practice shows you how to confidently develop a secure system step by step.